2019
DOI: 10.1016/j.ebiom.2019.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Modified Mediterranean-ketogenic diet modulates gut microbiome and short-chain fatty acids in association with Alzheimer's disease markers in subjects with mild cognitive impairment

Abstract: BackgroundAlzheimer's disease (AD) prevalence is increasing, but its etiology remains elusive. Gut microbes can contribute to AD pathology and may help identifying novel markers and therapies against AD. Herein, we examine how the gut microbiome differs in older adults with mild cognitive impairment compared to cognitively normal counterparts, and whether and how a modified Mediterranean-ketogenic diet (MMKD) alters the gut microbiome signature in association with cerebrospinal fluid (CSF) AD biomarkers.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
407
3
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 437 publications
(430 citation statements)
references
References 59 publications
16
407
3
4
Order By: Relevance
“…A cross-sectional study reported lower abundance of Bacteroides genus in the gut microbiota of dementia patients [51]. Furthermore, individuals with mild cognitive impairment have a significantly higher abundance of phylum Proteobacteria compared to cognitively healthy participants [52]. In our current study, the correlation analysis further illustrated a significant association between the abundance of phylum Bacteroidetes and Proteobacteria with cognition index in nesting behavioral and temporal order memory tests.…”
Section: Discussionsupporting
confidence: 70%
“…A cross-sectional study reported lower abundance of Bacteroides genus in the gut microbiota of dementia patients [51]. Furthermore, individuals with mild cognitive impairment have a significantly higher abundance of phylum Proteobacteria compared to cognitively healthy participants [52]. In our current study, the correlation analysis further illustrated a significant association between the abundance of phylum Bacteroidetes and Proteobacteria with cognition index in nesting behavioral and temporal order memory tests.…”
Section: Discussionsupporting
confidence: 70%
“…Firmicutes covers the majority of butyrate-producing bacteria in human bacterial communities, and is known for its function in transforming undigested proteins and carbohydrates into acetic acid, and producing energy for the organism of host [12]. Meanwhile, the crucial short-chain fatty acids (SCFAs) butyrate participates in activating multiple physiological signal pathways, such as anti-inflammatory activities, and the differentiation and proliferation of regulatory T cells [13,14]. Under this circumstance, the lower abundance of Firmicutes in present study may be more reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that microbiota-derived products may be act as triggers for promoting a proinflammatory and metabolically dysfunctional environment in WD patients. Microbiota-produced butyrate has been reported to provide energy for colonocytes and then prevent autophagy in the intestine of host [13]. Additionally, physiological homeostasis may be disrupted by gut microbiota, resulting in host metabolism disruption, and immune, neurological or cognitive system dysregulation and others [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…274 Dietary changes in patients with MCI also appear to alter the microbiota population and their association with Aβ and p-Tau levels in the CSF. 275 These data convey how peripheral inflammation induced by dysbiosis in the gut can have broad clinical applications for mitigating AD risk and pathology in the future.…”
Section: Role Of Age Environmental Factors and Sex In Admentioning
confidence: 96%